Spinal deformities the essentials - Heary, Robert F.; Albert, Todd J. (Thieme Medical Publishers, 2014)
Spinal Deformities: The Essentials, Second Edition presents a detailed overview of current key principles and practices involved in the diagnosis and treatment of patients with spinal deformities. Each chapter of this introductory text begins with The Essentials, a bulleted list that summarizes the most important concepts presented, providing busy surgeons, residents, and fellows with a quick refresher before surgery.